Feasibility and validity of ambulant biofeedback devices to improve weight-bearing compliance in trauma patients with lower extremity fractures: A narrative review - Eline M. Jagtenberg; Pishtiwan H. Kalmet; Maartje A. Krom; Taco J. Blokhuis; Henk A.M. Seelen; Martijn Poeze (Medical Journals Sweden, 2020)
Background: Ambulant biofeedback devices can be used to provide real-time feedback for trauma patients on weight-bearing regimes. The devices also enable prescribing clinicians to monitor and train patients' level of weight-bearing. However, there is limited evidence regarding the feasibility of use of such devices in controlling weight-bearing, and their full potential remains to be elucidated. Objective: To investigate the feasibility of using ambulant biofeedback training devices to improve compliance with weight-bearing regimes in trauma patients with lower extremity fractures. Methods: A literature review of the feasibility and clinical validity of ambulant biofeedback devices. Results: Three clinically validated biofeedback devices were found feasible for use in monitoring the compliance of patients who have lower extremity fractures with different weight-bearing regimes. Conclusion: Further information about the feasibility and clinical validity of biofeedback training devices is nee-ded in order to optimize weight-bearing instructions for patients.